(untitled) (Asian Journal of Medical and Biological Research, 2022)
A variety of fishes consumed regularly are prone to pathogenic spoilage especially by different microbes. It is important to find out microbiological quality of fish that we consume regularly to protect the public health. Current research was conducted to assess the incidence of Salmonella and Escherichia coli (E. coli) contamination in three selected catfish species namely, Ayer (Sperata seenghala), Pabda (Ompok pabda) and Magur (Clarias batrachus) of five rivers (Dhepa, Atrai, Punorvoba, Kakra, and Ghorveshori) of Dinajpur district. The study showed that Salmonella and E. coli positive isolates were 33.33% and 55.55% in Punorvoba river, 31.03% and 50.00% in Atrai river, 30.19% and 56.60% in Dhepa river, 29.63% and 59.26% in Ghorveshori river and 27.08% and 56.25% in Kakra river, respectively. Highest percentage of Salmonella and E. coli were found in Ompok pabda (39.40%) and in Clarias batrachus (63.84%), respectively. Lowest percentage of Salmonella and E. coli were found in Sperata seenghala (26.50% and 41.07%), respectively. The percentage of E. coli was greater than Salmonella for each of the experimental samples that are very alarming for consumption of wild catfish. At the same time, the microbial quality of water of Dhepa, Atrai, Punorvoba, Kakra, and Ghorveshori rivers are not satisfactory regarding fish consumption and public health. Asian J. Med. Biol. Res. 2022, 8 (1), 9-15